Efficient voltage control strategy: observability design for multistage DC–DC buck converter - Albariqi, Khalid A.; Alhussainy, Abdullah Ali; Bawayan, Haneen; Alturki, Yusuf A.; Alghamdi, Sultan (Frontiers in Energy Research, 2024)
This paper emphasizes the significance of implementing an effective control system to enhance the performance of a three-stage DC-DC buck Converter (TDDC). In this paper, we present the development of an observation controller (OC) for TDDC. Average modeling of the DC-DC converter was employed alongside an observer algorithm to design the OC for TDDC. The primary focus is the adoption of an observation topology aimed at enhancing the system's responsiveness under various conditions, including variable input voltages, reference voltage changes, load fluctuations, integration with PV, and charging the battery. This approach ensures improved stability and performance, addressing the dynamic challenges inherent in such systems. A comparative analysis is conducted on two distinct control topologies for the proposed TDDC system: PI and advanced OC. MATLAB Simulink is employed to model and simulate the proposed system. The results demonstrate a reduction in the rise time and settling time of TDDC when OC and PI were implemented, respectively. Additionally, they eliminate the 20% overshoot for the system with the PI controller. With the OC, the output voltage oscillations are minimized from 13% to 2%, as compared to PI. The OC was integrated into TDDC to enhance stability and improve the control loops, particularly the third loop. These improvements make the TDDC with OC suitable for applications in renewable energy systems, microgrids, telecommunications, and electric vehicles, where precise control and stability are essential.